Cost-effective 17O enrichment and NMR spectroscopy of mixed-metal terephthalate metal–organic frameworks. Issue 4 (28th November 2017) - Bignami, Giulia P. M.; Davis, Zachary H.; Dawson, Daniel M.; Morris, Samuel A.; Russell, Samantha E.; McKay, David; Parke, Richard E.; Iuga, Dinu; Morris, Russell E.; Ashbrook, Sharon E.
Abstract : Cost-effective 17 O enrichment of metal–organic frameworks enables the composition and disorder in mixed-metal materials to be determined using NMR spectroscopy. Abstract : 17 O solid-state NMR spectroscopy is employed to investigate the cation disorder in metal–organic frameworks containing two different types of metal cations. Although NMR offers exquisite sensitivity to the local, atomic-scale structure, making it an ideal tool for the characterisation of disordered materials, the low natural abundance of 17 O (0.037%) necessitates expensive isotopic enrichment to acquire spectra on a reasonable timescale. Using dry gel conversion and a novel steaming method we show that cost-effective and atom-efficient enrichment of MOFs is possible, and that high-resolution 17 O NMR spectra are sensitive both to the structural forms of the MOF and the presence of guest molecules. For mixed-metal forms of MIL-53, NMR can also provide information on the final composition of the materials (notably different to that of the initial starting material) and the preference for cation clustering/ordering within the MOFs. For Al, Ga MIL-53, the distribution of cations results in a mixed-pore form upon exposure to water, unlike the different structures seen for the corresponding end members. This work shows that as good levels of enrichment can be achieved at reasonable cost, 17 O NMR spectroscopy should be an invaluable tool for the study of these important functional materials.